Evolution of studies on subvertising: a scoping review - Inés Leal-Rico; Natalia Papí-Gálvez; Cande Sánchez-Olmos (Humanities & Social Sciences Communications)
Abstract Subvertising is a communication phenomenon aimed at eliciting a response from citizens to advertising messages, and provides tools to fight back on a symbolic battleground. Within the current communication paradigm, subvertising stands as a form of empowerment for a better informed and more participatory active audience. Subvertising practices provide a communication response to a corporate discourse that is considered by many collectives to be manipulative and excessive in its omnipresence. Given that subvertising is such a practical phenomenon, it seems relevant to review what theoretical contributions have been made and determine the current state of research into the subject. This article presents a scoping review of publications on subvertising from 1980 through to March 2020, the main objective being to determine the intellectual output and evolution of existing research, with in-depth analysis of the texts and studies identified. The review process was carried out by searching 11 national and international databases, using 19 keywords selected in a preliminary narrative phase. The results show the evolution of existing literature by country of publication, language, document type, journal, authorship and document features. The conclusions reached indicate that the number of publications on the phenomenon of subvertising is on the rise, attracting interest from a wide range of disciplines, not solely those relating to communication.